Lipid oxidation products of heated soybeans as a possible cause of protection from ruminal biohydrogenation. Issue 2 (17th December 2012) - Kaleem, Muhammad; Farizon, Yves; Enjalbert, Francis; Troegeler‐Meynadier, Annabelle
Abstract Heating oilseeds has been shown to improve the milk fatty acid profile when given to dairy cows, compared to raw oilseeds. However, results from published studies are conflicting. The conditions of heating and storage of the oilseeds could be responsible for these differences, probably partly through their effects on lipid oxidation, the products of which could act on ruminal biohydrogenation (BH). Thus, 15 different treatments were applied to ground soybeans: three levels of heating (no heating, 30 min at 110 or 150°C) × 5 ambient storage durations (0, 1, 2, 4, or 6 months). Soybeans were incubated in vitro with ruminal fluid for 6 h. Triacylglycerol (TAG) polymers, hydroperoxides and hydroxyacids (HOA), aldehydes, and fatty acids were assayed in soybeans and ruminal culture. No TAG polymer was detected in any treatment. Soybeans stored for a long time had a high content of HOA, whereas those heated at 150°C, whatever the storage duration, had high aldehyde contents. The percentage disappearance of cis‐9, cis‐12 18:2 and cis‐9, cis‐12, cis‐15 18:3 in incubates decreased significantly in cultures with heated soybeans, especially at 150°C, suggesting that this partial protection of polyunsaturated fatty acids (PUFA) from BH was at least in part linked to the aldehyde content of the heated soybeans. Practical applications: Oilseeds given to ruminants are often heated, and heat treatment is known to generate oxidation products. Knowing what oxidation products influence ruminal biohydrogenation of unsaturated fatty acids could result in technological processes allowing a better transfer of unsaturated fatty acids from oilseeds to ruminant products.